1977
DOI: 10.1016/0014-5793(77)80139-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP in Dictyostelium discoideum Oscillations and pulses in response to folic acid and cyclic AMP signals

Abstract: Cells of Dictyostelium discoideum respond chemotactically to.cyclic AMP [l] and to folic acid [3]. Cyclic AMP is a most efficient attractant for cells of the aggregation phase [2], folic acid is more effective with preaggregation cells [4]. Both cyclic AMP and folic acid stimulate also cell development from the preaggregation phase to the aggregation competent state [S-8]. During this process the cells acquire the capacity to synthesize cyclic AMP periodically, and to release it into the extracellular space i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(102 citation statements)
references
References 16 publications
2
100
0
Order By: Relevance
“…Which form of phosphodiesterase plays the most important role in controlling the cGMP content in intact cells is not known. These results indicate a role of cGMP during chemotaxis in D. discoideum, cAMP and frolic acid not only induce chemotaxis [2,3] but also cell differentiation [25][26][27] and, in the case of cAMP, adenylate cyclase activation [28]. More information is required to know which of these biological effects are regulated by cGMP.…”
Section: Discussionmentioning
confidence: 97%
“…Which form of phosphodiesterase plays the most important role in controlling the cGMP content in intact cells is not known. These results indicate a role of cGMP during chemotaxis in D. discoideum, cAMP and frolic acid not only induce chemotaxis [2,3] but also cell differentiation [25][26][27] and, in the case of cAMP, adenylate cyclase activation [28]. More information is required to know which of these biological effects are regulated by cGMP.…”
Section: Discussionmentioning
confidence: 97%
“…ADP supported 38% of the activity of ATP. cAMP and cyclic GMP, which seems to be involved in the transduction of a chemotactic signal in D. discoideum (9,17), also had no effect on Ca2+ uptake. The mitochondrial uncouplers, 2,4-dinitrophenol (0.1 mM), NaN3 (0.1 mM), oligomycin (0.7,gg/ml), and ruthenium red (3 nmol/mg of protein, inhibited Ca2+ uptake by not more than 10%.…”
mentioning
confidence: 93%
“…Pan et al (11) identified the chemotactic agent as folic acid. The addition of folate during early development results in the activation of guanylyl and adenylyl cyclases, the rapid association of actin with the cytoskeleton, and chemotactic movement, similar to responses that are elicited by cAMP during aggregation (12)(13)(14). Tillinghast and Newell (14) showed that vegetative cells and mound-stage cells differentially exhibit chemotaxis to different folate analogues, suggesting the presence of more than one class of folate receptor (FAR).…”
mentioning
confidence: 95%